STRATEGI PENGEMBANGAN USAHA UD. BARUASA MEMBIRI DALAM MENINGKATKAN PENDAPATAN - Muh. Ikhsan; Akbar Wahbi; Bakti; Jamal; Waode Harliyanti Unga; Muh. Aswin (Halu Oleo University, 2025)
This study aims to analyse business development strategies to increase revenue at UD. Baruasa Membiri in Kendari City. Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the regional economy, particularly in maintaining business sustainability and enhancing competitiveness. In facing increasingly intense competition, UD. Baruasa Membiri implements various business development strategies, such as product diversification, market share expansion, and partnerships and collaborations. The research method used is a descriptive qualitative approach with SWOT analysis techniques. Data were obtained through observations, interviews, and documentation from the owner and employees of UD. Baruasa Membiri. The results of the study indicate that the implemented business development strategies contribute to revenue growth, despite challenges in marketing and product innovation. By optimising internal strengths and external opportunities, UD. Baruasa Membiri can enhance its income and achieve sustainable business growth.